The Phosphoproteomes of Plasmodium falciparum and Toxoplasma gondii Reveal Unusual Adaptations Within and Beyond the Parasites' Boundaries - Treeck, Moritz; Sanders, John L.; Elias, Joshua E.; Boothroyd, John C. (Cell host & microbe, 2011)
Plasmodium falciparum and Toxoplasma gondii are obligate intracellular apicomplexan parasites that rapidly invade and extensively modify host cells. Protein phosphorylation is one mechanism by which these parasites can control such processes. Here we present a phosphoproteome analysis of peptides enriched from schizont stage P. falciparum and T. gondii tachyzoites that are either “intracellular” or purified away from host material. Using liquid chromatography-tandem mass spectrometry, we identified over 5,000 and 10,000 previously unknown phosphorylation sites in P. falciparum and T. gondii, respectively, revealing that protein phosphorylation is an extensively used regulation mechanism both within and beyond parasite boundaries. Unexpectedly, both parasites have phosphorylated tyrosines, and P. falciparum has unusual phosphorylation motifs that are apparently shaped by its A:T-rich genome. This data set provides important information on the role of phosphorylation in the host-pathogen interaction and clues to the evolutionary forces operating on protein phosphorylation motifs in both parasites. ► Proteome-wide analysis of phosphorylation sites in P. falciparum and T. gondii ► Evidence for tyrosine phosphorylation was found in both parasites ► P. falciparum shows unusual phosphorylation-site motif usage ► We describe a method to identify phosphorylation beyond a parasite's boundary